2009
DOI: 10.1007/s11483-009-9123-x
|View full text |Cite
|
Sign up to set email alerts
|

New Strategies of LIBS-Based Validation of Glycemic Elements for Diabetes Management

Abstract: Antidiabetic efficacy of medicinal plant cannot be ignored in order to develop drugs without toxicity and side effects. Trace elements present in plant material is responsible for their medicinal nature and hence it is necessary to know the major and minor constituents of the plant material. Laser-induced breakdown spectroscopy (LIBS) is a very efficient and powerful analytical tool to monitor the elements present in sample. The present study deals with the LIBS-based validation of glycemic elements present in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…29 Recently, we have found in our lab that Mg and Ca manage the blood glucose levels and also restore the antioxidant activity in type 2 diabetic rats. [30][31][32][33][34] From the outcome of this study, it can be conclusively stated that the higher concentrations of Ca ++ , Mg ++ , and Fe ++ , as reflected by their intensities, are responsible for glycemic potential of T. dioica. Further studies to establish the absolute concentrations of trace elements needed for optimum glycemic activity in diabetic management are in progress.…”
Section: Resultsmentioning
confidence: 58%
“…29 Recently, we have found in our lab that Mg and Ca manage the blood glucose levels and also restore the antioxidant activity in type 2 diabetic rats. [30][31][32][33][34] From the outcome of this study, it can be conclusively stated that the higher concentrations of Ca ++ , Mg ++ , and Fe ++ , as reflected by their intensities, are responsible for glycemic potential of T. dioica. Further studies to establish the absolute concentrations of trace elements needed for optimum glycemic activity in diabetic management are in progress.…”
Section: Resultsmentioning
confidence: 58%
“…IR and UV spectra were recorded on Perkin-Elmer 599 B and Shimadzu UV-250 spectrometers respectively. 1 H NMR, 13 C NMR, spectra were recorded in DMSO-d 6 on Bruker 300 DPX, FT NMR ( 1 H: 400 MHz, 13 C: 100 MHz) spectrometers. Mass spectra were measured on a JEOL AX 500 spectrometer.…”
Section: Characterization Of Compoundsmentioning
confidence: 99%
“…Molecular formulas of both the unknown compounds were established by their elemental and spectral analysis viz. UV, IR, 1 H and 13 C NMR as follows: C-6΄ positions respectively. Furthermore, these spectral data are in agreement with the earlier reports of literature 5,16,17 .…”
Section: Isolation Of Compoundmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Rai et al has also postulated the utility of LIBS technique on the plant product. 8,[12][13][14][15] Emblica officinalis (Family Euphorbiaceae) has been extensively used in traditional Indian system of medicine as an important constituent for scavenging reactive oxygen species. 16 The available reports indicated that different parts of E. officinalis have been used as anti-cancer, 17 antimutagenic, 18 antidiabetic, 19 hepatoprotective, 18 and also as antiulcer agents.…”
Section: Introductionmentioning
confidence: 99%